The Intra Industry Trade between Portugal European Union, Portugal Spain, Portugal-France, Portugal Germany, Portugal-Ireland, Portugal-Greece and Portugal-Netherlands - a Dynamic Panel Data Analysis (1996-2000) - Horácio Faustino; Nuno Carlos Leit\~ao (European Regional Science Association (ERSA), 2005)
Portugal's main trade partners have been Spain, Germany and France. In this paper we analyse the intra industry trade in the manufacturing industry between Portugal Spain, Portugal-France, Portugal Germany, Portugal-Ireland and Portugal-Greece. We also present the results of intra industry trade (IIT) between Portugal and the European Union. The innovation, technological progress, human capital, and scale economies are some of the explicative variables of the intra industry trade phenomena. This type of trade is associated with the product differentiation. We consider the panel data models, which are commonly used in the literature, and the recent GMM estimator. One of the objectives of this paper is to verify the estimated models of intra industry trade (IIT), horizontal intra industry trade (HIIT), and vertical intra industry trade (VIIT), and to also verify if the results obtained are different for the partners in analysis. The second objective is to test if the relationship between HIIT and VIIT is determinate by comparative advantages. The third propose is to analyse the results for IIT,HIIT and VIIT with the GMM estimator, and to observe if the models have autocorrelation or specification problems. We will use the m statistics test of Arellano and Bond (1991) and the methodology of Blundell and Bond (1998,2000) to estimated the models.
Keywords: 330